PERLINDUNGAN HUTAN ADAT AEK NAPA DI DESA SABUNGAN NI HUTA IV KECAMATAN SIPAHUTAR KABUPATEN TAPANULI UTARA PASCA DIKELUARKAN KEPUTUSAN MENTERI KEHUTANAN NOMOR 579 TAHUN 2014 TENTANG KAWASAN HUTAN PROVINSI SUMATERA UTARA - ROBBY MARSHEL SINAGA (PREMISE LAW JURNAL, 2017)
Customary (Adat) Forest is a forest ruled by the customary law community. It is generally formed from a natural forest which is managed and collectively used for the social, economic and cultural sake from generation to generation. After the issuance of the Ruling of the Constitutional Court No. 35/pii-x/2012 the customary law community, in whose region customary forest is located, is no longer paid attention to by the government because there is no regulations of local government which acknowledges the existence of the customary law community and their forest. This is an empirical legal research which objective is to involve the researcher to not only think about normative legal problems (las as written in book), which are technical in executing the legal provisions like a machine which creates and produces a particular product through a mechanical proces. Keywords: Protection for Customary Forest